2020
DOI: 10.1073/pnas.2007332117
|View full text |Cite
|
Sign up to set email alerts
|

Mobile loop dynamics in adenosyltransferase control binding and reactivity of coenzyme B 12

Abstract: Cobalamin is a complex organometallic cofactor that is processed and targeted via a network of chaperones to its dependent enzymes. AdoCbl (5′-deoxyadenosylcobalamin) is synthesized from cob(II)alamin in a reductive adenosylation reaction catalyzed by adenosyltransferase (ATR), which also serves as an escort, delivering AdoCbl to methylmalonyl-CoA mutase (MCM). The mechanism by which ATR signals that its cofactor cargo is ready (AdoCbl) or not [cob(II)alamin] for transfer to MCM, is not known. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…In this structure, a complete ordering of loops, except for the first 50 residues, was observed. As seen previously ( 16 ), ATP induced ordering of residues 68 to 80 into a β-hairpin, forming the roof of the active site ( Fig. 6 B ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In this structure, a complete ordering of loops, except for the first 50 residues, was observed. As seen previously ( 16 ), ATP induced ordering of residues 68 to 80 into a β-hairpin, forming the roof of the active site ( Fig. 6 B ).…”
Section: Resultssupporting
confidence: 81%
“…The base in the base-on form of cobalamin refers specifically to DMB. Crystallographic snapshots of the homologous ATR from Mycobacterium tuberculosis have revealed the importance of protein and cofactor tail dynamics in controlling cofactor coordination and reactivity ( 16 ). In the presence of ATP and cob(II)alamin, the N-terminus of ATR becomes ordered, forming a cup shaped structure that forces the DMB tail into a side pocket.…”
mentioning
confidence: 99%
“…Sci. U. S. A.20201173041230422 An Interprotein Co–S Coordination Complex in the B 12 -Trafficking PathwayLiZ.MascarenhasR.TwahirU.…”
Section: Key Referencesmentioning
confidence: 99%
“…Extensive biochemical characterization of bacterial PduO-type adenosyltransferases, a class to which MMAB also belongs, has illustrated their unique reaction mechanism (Johnson et al 2004;Mera et al 2007;Padovani et al 2008;St. Maurice et al 2008;Padovani and Banerjee 2009;Park et al 2012;Mascarenhas et al 2020). These studies have demonstrated that ATP binds to one of three potential active-sites, each occurring at the homotrimer subunit interfaces, following which cobalamin binds to the same site in the base-off state.…”
Section: Introductionmentioning
confidence: 99%